The Relationship between Gender Stereotype Perception and Career Interest in Nursing in Male Nursing Students at Gorontalo State University - Nis Fenti Tongkonoo; Zuhriana K. Yusuf; Nirwanto K. Rahim (Universitas Muhammadiyah Palu, 2026)
The perception of gender stereotypes is still an issue inherent in the nursing profession, especially for male nursing students. The view that nursing is an identical profession to women can influence the interest of male students in planning and determining a career in nursing. This study aims to determine the relationship between the perception of gender stereotypes and the career interests of male nursing students at Gorontalo State University. This study uses a correlational analytical design with a cross sectional approach. The research sample amounted to 76 male nursing students who were taken using the total sampling technique. Data collection was carried out using questionnaires on the perception of gender stereotypes and career interests, while data analysis used the Spearman Rank test. The results showed that most students had a positive perception of gender stereotypes as many as 60 respondents (78.9%), and career interest was in the high category as many as 40 respondents (52.6%). The results of the Spearman Rank test obtained a p-value = 0.000 (p < 0.05), which shows that there is a relationship between the perception of gender stereotypes and interest in a career as a nurse in male nursing students at Gorontalo State University. So based on the results of this study, it is hoped that the campus, especially the nursing department, can increase education and support efforts to build a positive perception of the nursing profession in male students.